Republic of Uzbekistan : Living Standards Assessment Update - World Bank (Washington, DC, 2012)
The purpose of this living standards assessment is to update and expand the first living standards assessment report that documented the poverty situation in Uzbekistan in 2000/2001. Attention has been paid to ensure the comparability of the analysis of the three years of data. The data themselves are largely comparable: the sampling methods have remained the same, as have the questionnaires and the basic implementation of the survey. However, some changes have occurred, primarily due to improved field work: these have been taken into account in the present analysis. The chapter is divided into three parts. An overview of the welfare levels in Uzbekistan from 2000-01 through 2003 is presented in section one, along with a discussion about the data sources and their strengths and weaknesses for multi-year analysis, and an analysis of the relationship between economic growth and welfare. In section two the basic indicators of living standards over the time period are presented. Section three contains information on two topics of interest for short-term and medium-term welfare: labor and education.